Muslim rulers and rebels everyday politics and armed separatism in the southern Philippines - McKenna, Thomas M. 1952- (Berkeley, [California] University of California Press, 1998)
An account of the Muslim separatist rebellion in the Philippines. It examines Muslim separatism against a background of more than four hundred years of political relations among indigenous Muslim rulers, their subjects, and external powers seeking the subjugation of Philippine Muslims.
INTRODUCTION. Extraordinary and Everyday Politics in the Muslim Philippines -- CHAPTER I. The Politics of Heritage -- CHAPTER 2. People and Territory in Cotabato -- CHAPTER 3. Islamic Rule in Cotabato -- CHAPTER 4. European Impositions and the Myth of Morohood -- CHAPTER 5. America?s Moros -- CHAPTER 6. Postcolonial Transitions -- CHAPTER 7. Muslim Separatism and the Bangsamoro Rebellion -- CHAPTER 8. Regarding the War from Campo Muslim -- CHAPTER 9. Unarmed Struggle -- CHAPTER 10. Muslim Nationalism after Marcos -- CHAPTER 11. Resistance and Rule in Cotabato -- Notes.
Includes bibliographical references (pages 339-353) and index.
Electronic reproduction.
Keywords: Moro National Liberation Front; Muslims -- Philippines -- Cotabato City Region; Muslims -- Politics and government. -- Philippines -- Mindanao Island; Electronic books; Cotabato City Region (Philippines) -- Politics and government; Mindanao Island (Philippines) -- History -- Autonomy and independence movements